(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wijayanti M, Wahyudi AT, Yuhana M, Engelhaupt M, Meryandini A. 2019. Impact of Bukit Dua Belas rainforest transformation to oil palm plantation on phylogenetic of soil bacterial communities in Sarolangun, Jambi, Sumatra, Indonesia. Biodiversitas 20: 811-818. Land use change from forest to oil palm plantation at Sumatra could decrease biodiversity, including bacterial diversity. The case of Bukit Dua Belas transformation from forest to oil palm plantation was gotten for measuring shift community of soil bacterial in both areas. The diversity of bacterial communities from rainforest and oil palm plantation topsoil in Sumatra was studied using pyrosequencing of 16S rRNA gene and common biodiversity indices. Phylogenetic approach was used to reveal the community shift of bacterial phyla and genera in both areas. Ecological approach was carried out by measuring soil pH, TC (total carbon), TN (total nitrogen), AP (available phosphorous), bacterial diversity with Shannon and Simpson indices, and bacterial richness with Chao1-ACE index and OTUs. Bacterial diversity and richness on lowland forest topsoil and oil palm plantation soil were not different, as soil pH, TC, and TN as substrate factors were not different significantly. The majority of sequences related to Acidobacteria (56.33%), Proteobacteria (27.43%), Actinobacteria (7.11%), and Cyanobacteria (5.55%) were from forest; whereas those related to Acidobacteria (50.11%), Proteobacteria (31.63%), Actinobacteria (7.58%), Chloroflexi (2.60%), and Gemmatimonadetes (2.71%) invented from oil palm plantation. Acidobacteria was the most dominant phyla in both habitats, because soil pH in both areas was acidic (3.77 - 4.80 pHH2O). The genera of alpha-proteobacteria dominated in genera phylotype of bacterial 16S rRNA phylogenetic revealed in both forest and oil palm plantation topsoil. The most genera in phylogenetic tree are Burkholderia from Beta-proteobacteria. The bacterial community shift occurred in forest transformation, even though the oil palm plantation showed more bacterial phyla and genera than the lowland rainforest.